2018
DOI: 10.1016/j.japh.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of athletes and pharmacists on pharmacist-provided sports supplement counseling: An exploratory study

Abstract: Pharmacists were not identified as a primary resource for sports supplements, but athletes would be willing to discuss this topic with knowledgeable and physically fit pharmacists. Pharmacists felt that they lacked knowledge and confidence regarding sports supplement products but noted enthusiasm to provide counseling. Sports pharmacy counseling could be a viable expansion of pharmacy services in community pharmacies with proper education and tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…Findings of this Australian study are consistent with the reports of international studies in which pharmacists self-reported that their knowledge and awareness of doping, anti-doping and sport supplements are low [13,15,16]. Additionally, pharmacists reported low confidence [15] and difficulty finding reliable, evidence-based information about drugs in sport and sport supplements [17]. Another study in Qatar showed that 60% of pharmacist respondents were unaware of WADA's role in doping.…”
Section: Discussionsupporting
confidence: 85%
“…Findings of this Australian study are consistent with the reports of international studies in which pharmacists self-reported that their knowledge and awareness of doping, anti-doping and sport supplements are low [13,15,16]. Additionally, pharmacists reported low confidence [15] and difficulty finding reliable, evidence-based information about drugs in sport and sport supplements [17]. Another study in Qatar showed that 60% of pharmacist respondents were unaware of WADA's role in doping.…”
Section: Discussionsupporting
confidence: 85%
“…Study design of most (81.8%) of the studies was “observational” [19,20,23,29,30,31,32,33,34,35] with only one “experimental” design [36]. Although observational cross-sectional studies have a place in research, particularly in emerging fields such as sports pharmacy, most ( n = 7/11) used convenience sampling [19,20,29,31,33,35,36] and all utilized surveys, which were piloted only for face validity or content validity. This may be due to a lack of funding since only one of the studies was supported by an external granting agency [32].…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacists consider themselves a good potential source of drug information for athletes [19,31,32], and, while pharmacists are enthusiastic about counseling athletes, few feel equipped to do so [29,31,32,34]. Key barriers identified by pharmacists were a lack of knowledge about prohibited lists, not knowing where to source reliable information about banned substances, and a lack of confidence in discussing doping with athletes [19,36]. Other barriers included time, a perceived lack of evidence about the benefits of sports supplements, and a limited range of sports supplement products stocked by pharmacy outlets [19,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a US study, community pharmacists wish to provide information related to the nutritional supplement intake of athletes, but lack of time and knowledge prevent them from these activities (Howard et al, 2018). The same study also showed, in cross-sectional study of athletes, that athletes did not regard pharmacists as information providers of sports supplements, but wished to ask them about supplements (Howard et al, 2018). It is expected that providing nutritional and supplement intake advice and support will become important duties for pharmacists.…”
Section: Discussionmentioning
confidence: 99%